Treatment of Multifocal Multisystem BRAF Positive Langerhans Cell Histiocytosis with Cladribine, Surgery and Allogenic Stem Cell Transplantation - Gabalec, Filip; Šimkovič, Martin; Zavřelová, Alžběta; Kašparová, Petra; Morávková, Paula; Kopáčová, Marcela; Masopust, Václav; Žák, Pavel; Čáp, Jan; Radocha, Jakub (Acta medica (Hradec Kralove), 2017)
Langerhans cell histiocytosis (LCH) is a very rare disease in adults and as well a very rare cause of sellar expansion. The clinical presentation can be heterogeneous, from a single bone lesion to potentially fatal, widespread disease. We describe the difficulties with the diagnosis and treatment of LCH as well as successful treatment with cladribine chemotherapy and allogeneic stem cell transplantation.
Keywords: Stem Cell Transplantation; dospělí; Magnetic Resonance Imaging; Female; histiocytóza z Langerhansových buněk; Adult; výsledek terapie; ženské pohlaví; histiocytosis; biopsie; lidé; transplantace kmenových buněk; Immunosuppressive Agents; stem cell; magnetická rezonanční tomografie; Treatment Outcome; stupeň závažnosti nemoci; hypopituitarism; Proto-Oncogene Proteins B-raf; protoonkogenní proteiny B-Raf; hypofýza; Biopsy; kladribin; cladribine; Cladribine; Pituitary Gland; Severity of Illness Index; transplantation; Histiocytosis, Langerhans-Cell; imunosupresiva; Humans